The Comparison Between Indonesian Constitutional Court and Russian Constitutional Court - Lintje Anna Marpaung (International Conference On Law, Business and Governance (ICon-LBG), 2013)
After the third change of the basic Constitution 1945 being ratified, in the meantime of waiting the new formed Constitutional Court, People Deliberation Council (MPR) calls for the Supreme Court to do a functional interim as it has been stated in Verse III of Constitution 1945 transition as a result of the fourth change. The House of Representatives (DPR) and the government then form law on Constitutional Court. Hans Kalsen states that the implementation of constitutional regulation about legislation can be effectively guaranteed only if there is an organ other than legislative agency given a task to check out whether a law product is constitutional or not. For that purpose, there has to be a particular organ similar to a special court which is called constitutional court, or control towards the constitutionality of law judicial review given to ordinary court, especially Supreme Court like in the united States. This controlling Special organ is able to scrap the unconstitutional law all in all so that it cannot be applied y other organs.This authority is run by the institution of justice authority implementer which stands apart from the Supreme Court, or being a part of Constitutional Court. However, if standing on its own, Constitutional Court will be a new phenomenon in the world of constitution. Almost all developed democratic countries, do not have Constitutional Courts which stand alone. Up to now, there have been 78 countries which form their court by their own.